Double sine-Gordon class of universal coarsening dynamics in a spin-1 Bose gas - Siovitz, Ido; Glück, Anna-Maria E.; Deller, Yannick; Schmutz, Alexander; Klein, Felix; Strobel, Helmut; Oberthaler, Markus K.; Gasenzer, Thomas (Physical review, 2025)
Far from equilibrium, universal dynamics prevails in many different situations, from pattern coarsening to turbulence. A central longstanding problem concerns the development of a theory of coarsening that rests on the microscopic properties of the system and allows identifying the interaction mechanisms underlying a possible overarching universality class of the associated scaling dynamics. In quantum systems, this is complicated by the existence of nonlinear and topological excitations due to the compact nature of phase degrees of freedom. We show that the double sine-Gordon model as a noncompact low-energy effective model of the spin-1 Bose gas accounts for subdiffusive coarsening dynamics, identifying field configurations spread over multiple wells of the sinusoidal potential as a precondition for the slow scaling. This is in contrast to diffusion-type scaling, which the model is known to exhibit as well, where field configurations are seen to not extend over more than two wells. Experimental observations of a spinor BEC support these characteristics, thus constituting a platform for the investigation of sine-Gordon dynamics. Our results point to a path towards a classification of pattern coarsening in many-body systems on the basis of microscopic models.